Corporate Environmental and Economic Performance of Japanese Manufacturing Firms: Empirical Study for Sustainable Development. (23rd October 2012) - Fujii, Hidemichi; Iwata, Kazuyuki; Kaneko, Shinji; Managi, Shunsuke
ABSTRACT This study examines the relationship between environmental performance and economic performance in Japanese manufacturing firms. The environmental performance indicators include CO2 emissions and the aggregate toxic risk associated with chemical emissions relative to sales. Return on assets (ROA) is used as an indicator of economic performance. We demonstrate that there is a significant inverted U‐shaped relationship between ROA and environmental performance calculated by aggregated toxic risk. We also find that the environmental performance increases ROA through both returns on sales and improved capital turnover. However, we observe a significant positive relationship between financial performance and environmental performance based on CO2 emissions. These findings may provide evidence for the consequences of firms' environmental behavior and sustainable development. Copyright © 2012 John Wiley & Sons, Ltd and ERP Environment.